Vesico-ureteral reflux surgery in children: Results of the Cohen technique. Preliminary communication - Pereyra Bonasso, Jorge (Cirugía del Uruguay, 1979)
Case material consisted of 35 children suffering from vesicoureteral reflux. 23 were treated surgically using Cohen's recently developed technique of ureteral "advance". It was applied in 36 hemisystems (including 3 duplicities: 39 ureteres) with 97,3 % good results, not with standing the fact that they were advanced cases with signs of renal lesion in 58 %. There follows a brief physiopathologic review and the conclusion that an earlier diagnosis of this condition is required.